Biomechanical Analysis of Suspension Training Push-Up. Issue 3 (March 2018) - Giancotti, Giuseppe F.; Fusco, Andrea; Varalda, Carlo; Capranica, Laura; Cortis, Cristina
Abstract : Abstract: Giancotti, GF, Fusco, A, Varalda, C, Capranica, L, and Cortis, C. Biomechanical analysis of suspension training push-up. J Strength Cond Res 32(3): 602–609, 2018—The aims of this study were to evaluate the load distribution between upper and lower extremities during suspension training (ST) push-up at different lengths of ST device and to predict useful equations to estimate the training load. After giving informed consent for participation, 25 subjects (17 men and 8 women; age = 28.1 ± 5.2 years; body mass = 69.4 ± 14.3 kg; height = 171.6 ± 11.3 cm; body mass index (BMI) = 23.4 ± 3.3 kg·m −2 ) were involved in the study. Each subject performed 14 static push-ups at 7 different lengths of ST device in 2 different elbow positions. The load distribution between upper and lower extremities was evaluated through a load cell and a force platform, respectively. To evaluate body inclination, all tests were recorded and analyzed through motion analysis software. To estimate the training load, a multilevel model regression ( p ⩽ 0.05) was used. Results showed that when the length of the ST device increased, the body inclination decreased, whereas the ground reaction force decreased and the load on the ST device increased. Moreover, when subjects moved from extended to flexed elbow, the ground reaction force decreased and the load on the ST device increased. In the created regression model (intraclass correlation coefficient = 0.24), the reaction force was the dependent variable, whereas the length of the ST device, BMI, and elbow position were the independent variables. The main findings were that the load distribution between upper and lower extremities changes both when modifying the body inclination and the length of the straps. The use of predicted equations could help practitioners to personalize the workouts according to different specific aims by modifying the length of the ST device to guarantee load progression.